Is carbonic anhydrase inhibition useful as a complementary therapy of Covid-19 infection? - Secil Deniz; Tugba Kevser Uysal; Clemente Capasso; Claudiu T. Supuran; Ozen Ozensoy Guler (Taylor & Francis Group, 2021)
The ongoing Covid-19 is a contagious disease, and it is characterised by different symptoms such as fever, cough, and shortness of breath. Rising concerns about Covid-19 have severely affected the healthcare system in all countries as the Covid-19 outbreak has developed at a rapid rate all around the globe. Intriguing, a clinically used drug, acetazolamide (a specific inhibitor of carbonic anhydrase, CA, EC 4.2.1.1), is used to treat high-altitude pulmonary oedema (HAPE), showing a high degree of clinical similarities with the pulmonary disease caused by Covid-19. In this context, this preliminary study aims to provide insights into some factors affecting the Covid-19 patients, such as hypoxaemia, hypoxia as well as the blood CA activity. We hypothesise that patients with Covid-19 problems could show a dysregulated acid-base status influenced by CA activity. These preliminary results suggest that the use of CA inhibitors as a pharmacological treatment for Covid-19 may be beneficial.